The Care and Feeding of the Computer: Imagining Machines' Preventive Care and Medicine. - Plotnick, Rachel (Information & Culture, 2023)
This article investigates how computing discourses, including user guides, news articles, and advertisements, urged personal computer users in the 1970s and 1980s to preventively care for their devices. Through hygiene recommendations related to eating, drinking, and dusting, these discourses warned that computers' "health" depended upon humans. Importantly, they interpreted care as individual responsibility by putting the onus on users to behave properly. Within this frame, such texts described repairs as unfortunate medical interventions resulting from neglect. The piece argues that computing discourses have historically defined "care" and "repair" in opposition, as acts of doting prevention and undesirable intervention, respectively.